TOWARDS A HARMONIOUS LABOUR-MANAGEMENT RELATIONS IN NIGERIAN PUBLIC UNIVERSITIES - ISA AMINU (International Studies Journal)
A harmonious labour management relation is a necessary precondition for academic excellence in the university system. Experiences in the Nigerian University system have however shown that all is not well with industrial harmony. Studies have been conducted on Labour management relations in the Nigerian public sector with little attention on contemporary issues that shapes the relationship in the Nigeria Public Universities. This paper examines contemporary issues in labour-management relations as it relates to the Nigerian Public Universities setting. It anchored on Neo-liberalism as its framework of analysis. The paper relied on secondary sources of data which were analysed using content analysis. Findings reveal that prevailing political, economic and other intervening variables such as globalization, economic recession, dominance of western model of democracy,emerging technology have always shapes government responses to the industrial crises in the Nigerian University system. The paper recommends that university unions must take cognize of them in their negotiations with the government for industrial harmony to prevail.